Microplastic Munchies: Exploring Microplastic Trophic Transfer Potential Between Two Key Prey Fish Species and Resident Common Bottlenose Dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida - Estella Martin; Randall S. Wells; Elizabeth J. Berens McCabe; Miranda K. Dziobak; Savannah M. Case; Tita Curtin; Eric Conger; Ayushi Gaur; Millie A. Knowles; Robyn Faulkner Allen; Christina N. Toms; John E. Weinstein; et al. (Marine Mammal Science, 2026)
Microplastics have been identified in hundreds of species, with evidence of trophic transfer via contaminated prey. Sarasota Bay common bottlenose dolphins ( Tursiops truncatus ) serve as sentinels of coastal pollution, including plastics and chemical plasticizers. Previous research confirmed microplastic ingestion in these dolphins (100.0%, n = 7) and extensive contamination in 11 common prey species (96.5%, n = 86). This study compared microplastic characteristics in dolphins, Gulf toadfish ( Opsanus beta , n = 30) and pinfish ( Lagodon rhomboides , n = 35), to assess potential trophic transfer. Dolphin ingestion was evaluated using gastric ( n = 23) and fecal ( n = 15) samples from catch‐and‐release health assessments (2022–2024), while prey gastrointestinal and muscle tissues were screened. Particles were prevalent across samples (dolphins: 82.6%, pinfish: 97.1%, toadfish: 96.7%), with fibers as the dominant shape. Raman spectroscopy confirmed plastic polymers (PL, PP, and PET) in all species. Pinfish had a higher median particle load (1.4 particles/g tissue) than toadfish (0.6 particles/g tissue; p = 0.006). Based on estimated daily food intake (5.96–6.45 kg) and diet composition (toadfish—34.1%, pinfish—38.1%), Sarasota dolphins may ingest more than 10,000 particles/day from these fish alone. Contaminated prey may be vectors for dolphin microplastic exposure. This study emphasizes the need for further research on microplastic pathways in marine food webs and implications for wildlife.